The impact of a 12-week intervention training program on gross motor coordination and strength in children playing Basketball - Koci, Ledina; Kotorri, Natasha; Bilali, Afrim (Edelweiss Applied Science and Technology, 2025)
This study investigates the effects of a 12-week coordination training program on gross motor coordination and strength in youth basketball players aged 10–12 years. A total of 96 participants (mean age = 11.3 ± 1.16 years) were divided into an intervention group (IG) and a control group (CG). The IG completed a structured coordination training program (15 minutes per session after the warm-up phase), in three sessions per week, while the CG followed their regular training routine (three sessions per week, routine training). Motor coordination was assessed using the KTK test battery and drop jump tests, while anthropometric measurements were also recorded. Results showed no significant differences in anthropometric measurements between the groups. However, the IG demonstrated significant improvements in motor coordination, particularly in lateral jumping, balance beam, and one-leg jumping tests (p < 0.05). Additionally, enhancements in lower-limb strength and power were observed, as reflected in improved drop jump Fmax, contact time, jumping height, and standing long jump performance tests (p < 0.05). These findings suggest that a targeted coordination training program can effectively enhance motor coordination, balance, agility, and lower-body strength in young basketball players, providing valuable insights for training and talent development in youth sports.